Совершенствование системы наклона кузова для скоростных поездов с силовым приводом на базе линейного двигателя - Омельяненко, Виктор Иванович; Кривякин, Геннадий Владимирович; Афанасьева, Елена Сергеевна (Українська державна академія залізничного транспорту, 2016)
Приведен краткий анализ различных типов силовых приводов, используемых в системах наклона кузовов скоростных поездов. Определены пути совершенствования системы наклона в части кинематической схемы и силового привода. Предложена кинематическая схема механизма наклона, которая позволяет существенно снизить величину усилия необходимого для поворота кузова на заданный угол. На основе исследования влияния электрофизических и геометрических параметров линейного электромеханического преобразователя на его рабочие свойства, разработан реверсивный линейный двигатель облегченной конструкции с тяговой характеристикой в максимальной степени соответствующей нагрузочной. Предложена мостовая схема питания линейных двигателей, обеспечивающая их синхронную работу.

The short analysis of the power drives various types that used at high-speed trains tilting system are provided. The improvement ways for tilting system at the part of the kinematic scheme and power drive are defined. The improved tilting mechanisms kinematic scheme that allows to substantially reduce a size of necessary effort for car body tilt at the set corner is offered. The tilt mechanism’s calculation chart and corresponded to it mathematical model that based at the static equilibrium system equalizations for tilt system’s load characteristic receipt are used. The facilitated construction reversible linear motor with linear form hauling characteristic are got on the base of linear electromechanics converter’s electrophisics and geometrics parameters at it working properties influence laws. The bridge power supply scheme for linear motors that provides its synchronously work and so allows to realize active system of the car body position management that influence on traveler comfort is developed.
The car body tilting system improvement for highspeed trains with a power drive based on a linear motor
Keywords: схема кинематическая; характеристика нагрузочная; двигатель реверсивный; high-speed train; linear motor; kinematic scheme; load characteristic